2017–2018 Florida Citrus Production Guide: Fresh Fruit Pesticide Residue Limits - Mark A. Ritenour (EDIS, 2017)
Current citrus production practices often include the use of various chemicals, many of which are pesticides. Chemical residues on the fruit after harvest are a concern to regulators and the public alike because of their potential negative health effects. Therefore, the US and other countries set maximum residue limits (MRLs) on fresh produce for various chemicals. This 5-page document is part of the 2017-2018 Florida Citrus Production Guide and discusses the MRLs for various chemicals used on Florida citrus. Written by Mark Ritenour and published by UF’s Horticultural Sciences Department, July 2017.